2009
DOI: 10.1089/fpd.2009.0266
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Source and Extended Virulence Genotypes ofEscherichia coliContaminating Retail Poultry Meat

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) are major players in human urinary tract infections, neonatal bacterial meningitis, and sepsis. Recently, it has been suggested that there might be a zoonotic component to these infections. To determine whether the E. coli contaminating retail poultry are possible extraintestinal pathogens, and to ascertain the source of these contaminants, they were assessed for their genetic similarities to E. coli incriminated in colibacillosis (avian pathogenic E. coli [A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 53 publications
6
42
0
4
Order By: Relevance
“…Similarly, 99 E. coli isolated from children with acute diarrhea were assigned to group A (59 strains), B1 (12 strains), B2 (9 strains) and D (19 strains). A similar result was reported in E. coli isolated from poultry and meat products in Minnesota and Wisconsin (16,17). It is interesting to note that the highest percentage of strains belonging to group A was found in the diarrhea cases which has no virulence determinants.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, 99 E. coli isolated from children with acute diarrhea were assigned to group A (59 strains), B1 (12 strains), B2 (9 strains) and D (19 strains). A similar result was reported in E. coli isolated from poultry and meat products in Minnesota and Wisconsin (16,17). It is interesting to note that the highest percentage of strains belonging to group A was found in the diarrhea cases which has no virulence determinants.…”
Section: Discussionsupporting
confidence: 81%
“…Further examination of our ExPEC collections showed that NMEC isolates harbored ColV and ColBM plasmids at ratios very similar to those for APEC isolates (Table 7). Certainly, there is evidence for a food-borne link between the two groups (25). At the very least, it appears that at least some NMEC isolates rely on these plasmid types for establishment of septicemia and/or meningitis in the neonatal human host.…”
Section: Discussionmentioning
confidence: 99%
“…Such similarities in the virulence traits found among APEC and other ExPEC subpathotypes have led to speculation that APEC has zoonotic potential (20,25,27) and may be a foodborne source of ExPEC causing disease in humans (10,14,18,22). Indeed, ExPEC strains have been identified in retail foods and poultry products (7,11,12,18), and at least one study has found avian isolates to be indistinguishable from human isolates (10).…”
mentioning
confidence: 99%